Transforming plant tissue culture with nanoparticles: A review of current applications - M.D.K.M. Gunasena; A.M.P.D. Alahakoon; K.P.G.D.M. Polwaththa; G.D.C.P. Galpaya; H.A.S.A. Priyanjani; K.R. Koswattage; W.T.P.S.K. Senarath (Plant Nano Biology)
The integration of nanotechnology into plant tissue culture represents a significant advancement in agricultural biotechnology. This review explores the transformative potential of nanoparticles in enhancing various processes within plant tissue culture. This review discussed how nanoparticles improve micropropagation efficiency by reducing contaminations, improving callus induction and increasing yields of secondary metabolites through cell suspension cultures. Additionally, the positive effects of nanoparticles on organogenesis, somatic embryogenesis, protoplast cultures and somaclonal variations are reviewed. Various types of nanoparticles, including silver, gold, zinc, cobalt, silica, and carbon-based nanoparticles, are analyzed for their specific applications and mechanisms of action. However, the potential toxicity of nanoparticles and their impact on plant health and the environment are critical concerns that are also reviewed. This comprehensive review provides insights into current applications, advantages and challenges of nanoparticle use in plant tissue culture, emphasizing the need for further research to optimize these innovative approaches for sustainable agricultural practices.